Visual analysis of traditional Chinese medicine nursing research on post-stroke sleep disorders based on CiteSpace (基于CiteSpace的脑卒中后睡眠障碍中医护理研究可视化分析) - GAO Ziqi (高子琪); LIAO Ruoyi (廖若夷); YU Yanlan (余艳兰); SI Huijie (佀惠婕); LIU Bin (刘彬); GUO Yuan (郭元) (中西医结合护理)
Objective To analyze the research hotspot and trend of Traditional Chinese Medicine (TCM) nursing of post-stroke sleep disorders based on CiteSpace, and provide reference for clinical nursing and scientific research. Methods The literature on TCM nursing of sleep disorders after stroke published by CNKI, Wanfang, VIP and CBM databases from January 31, 2023 was retrieved. The annual number of publications, authors, research institutions, keyword co-occurrence, keyword clustering and keyword timeline were analyzed by CiteSpace software. Results A total of 177 literatures met the requirements were retrieved, and the overall number of publications was on the rise. The cooperation network between the authors and research institutions was not yet mature. The bibliometric results showed that research hotspots of literatures wereextended care, emotion care and TCM nursing technology. Conclusion TCM nursing intervention for sleep disorders after stroke has achieved good results, which can significantly improve the sleep quality of patients, promote the outcome of the disease, and improve the quality of life of patients. (目的 使用CiteSpace工具对卒中后睡眠障碍进行分析, 为今后的临床护理和相关研究提供一定的帮助和参考。方法 检索关于卒中后睡眠障碍中医护理研究的文献, 主要检索的关键词包括脑卒中、卒中后睡眠障碍、睡眠障碍、中医护理、中医护理技术等, 检索数据库选择中国知网(CNKI)、万方(Wanfang Data)、维普(VIP)以及中国生物医学文献数据库(CBM), 时间截止到2023年1月31日, 使用CiteSpace软件进行分析, 主要包括年发文量、作者、研究机构、关键词共现、聚类、时间线等。结果 通过检索, 共计有177篇文献符合本次研究需求; 经过分析发现, 相关文献资料呈上升趋势, 逐年增加; 在研究中能看到相关的研究者和研究机构之间尚未形成成熟的合作关系网络; 同时, 卒中后睡眠障碍在中医研究中, 主要的研究焦点在于延续护理、情志护理以及中医护理技术等。结论 通过对相关文献的分析和整理发现, 针对卒中后睡眠障碍, 中医护理干预能够显著改善患者睡眠质量, 促进患者病情的改善和生活质量的提升, 在临床使用中有着非常理想的效果。)